An addressing on risk of mental health disorders through hybrid takaful (Islamic Insurance): a case of Malaysia / Khairil Faizal Khairi, Nur Hidayah Laili and Aimi Fadzirul Kamarubahrin - Khairi, Khairil Faizal; Laili, Nur Hidayah; Kamarubahrin, Aimi Fadzirul (Universiti Teknologi MARA, Perlis, 2021)
In addition to heart disease, other Malaysian extensive illnesses are mental health disorders. 29.2 per cent of Malaysians have recently suffered from mental illness, which has increased threefold compared to the previous year. The lowest income group accounts for the bulk of Malaysians suffering from mental illness. Currently, Singapore list among the countries has operative providing mental health insurance together with Australia, the United Kingdom and the United States of America. Malaysia is still far behind on offering mental health coverage with such a scheme only provided by AIA Malaysia. Therefore, through the takaful product, the purpose of this study is to address the risk of mental health disorders by hybrid takaful. The paper concluded that in order to maintain the promoting coverage and minimizing damage to mental health patients to human well-being, takaful mental health is needed in Malaysia market. In addition, this research would provide insight into the takaful industry for the development of a new and competitive product that could assist patients with a mental health disorder.